Gambaran Stres Pada Orang Tua dan Anak yang Mengalami Penyakit Leukemia: Literatur Review - Richa Pramaneta; Yufitriana Amir; Oswati Hasanah (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Leukemia is a malignant disease of Hematopoietic tissue which is characterized by the replacement of the marrow element from normal bone by abnormal/neoplastic blood cells. The main treatment for leukemia is chemotherapy. Chemotherapy treatment has side effects both physically and psychosocially. The first source of stress that occurs in parents is caused by children who are hospitalized, and then the second source of stress can be caused by the surrounding environment, the third source of stress is the treatment for children in accordance with medical procedures. Stress that occurs in children caused by anxiety and fear related to the whole process and the possibility of bodily injury, physical danger, and pain. This researcher used a literature review design using research journal searches using Google Scholar and PubMed with the keywords parent and child stress leukemia. There were 5 articles that matched the inclusion criteria followed by a matrix analysis based on the objectives, methods, samples, and research results. The results of the literature review show that the stress experienced by parents and children is categorized at moderate levels. This is to determine the level of stress for parents and children who experience leukemia.